2017
DOI: 10.3389/fpsyg.2017.01677
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Resilience? Sense of Coherence Is Associated between Lithuanian Survivors of Political Violence and Their Adult Offspring

Abstract: Little is known about intergeneration effects on mental health in the families of survivors of political oppression of communist regime in Central and Eastern Europe. We aimed to explore post-traumatic stress in the second generation of the Lithuanian survivors of political violence, and analyze links between parental and adult offsprings’ sense of coherence in the families exposed to political violence during the oppressive communist regime in Lithuania. A total of 110 matched pairs of communist regime politi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 53 publications
1
19
0
3
Order By: Relevance
“…Studies thus far suggest a population exposed to decades-long pervasive and systematic political oppression and violence during Soviet times (Kazlauskas & Zelviene, 2016). This includes experiences of forced displacement to remote regions of Northern Siberia, political imprisonment, abusive use of psychiatry, and other forms of repression (Kazlauskas, Gailiene, Vaskeliene, & Skeryte-Kazlauskiene, 2017). However, with a high prevalence of trauma in society, PTSD is not acknowledged in health care in Lithuania as it was evidenced by the recent analysis of the National health care registry in Lithuania .…”
mentioning
confidence: 99%
“…Studies thus far suggest a population exposed to decades-long pervasive and systematic political oppression and violence during Soviet times (Kazlauskas & Zelviene, 2016). This includes experiences of forced displacement to remote regions of Northern Siberia, political imprisonment, abusive use of psychiatry, and other forms of repression (Kazlauskas, Gailiene, Vaskeliene, & Skeryte-Kazlauskiene, 2017). However, with a high prevalence of trauma in society, PTSD is not acknowledged in health care in Lithuania as it was evidenced by the recent analysis of the National health care registry in Lithuania .…”
mentioning
confidence: 99%
“…A recent review reported 70-75% prevalence of traumatic events in the general population in Lithuania (21) similar to 68% prevalence of traumatic experiences in other European countries (22). However, several crosscultural studies revealed high prevalence of interpersonal violence in Lithuania including physical abuse in childhood (26.0%) (23) and domestic violence towards mother (16.5%) (24), and high levels of PTSD (30%) among second-generation survivors of political violence (25), indicating that Lithuanian population might have high rates of survivors of interpersonal trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Tokius skirtumus bandoma aiškinti tuo, kad atkūrus nepriklausomybę tarsi buvo pašalinta istorinė neteisybė: represijas patyrę žmonės buvo pripažinti nukentėjusiais (Bieliauskaitė ir kt., 2015). Tarpgeneracinis traumos ir atsparumo perdavimas randamas ne viename tyrime (Kazlauskas et al, 2017;Serbin & Karp, 2004). Mažulytė-Rašytinė (2017) atkreipia dėmesį, kad represijų poveikis geriau paaiškinamas, kai atsižvelgiama į santykius su artimaisiais.…”
Section: įVadasunclassified